Edukasi Klasifikasi Jenis-Jenis Sampah dan Penyediaan Tempat Sampah dari Bahan Daur Ulang di Desa Bungkuk Kecamatan Parang Kabupaten Magetan - Andhita Risko Faristiana; Dovano Anggres Wori; Linda Dwi Novita Wardani; Tazkiyatul Fikriyah (BADAN PENERBIT STIEPARI PRESS, 2023)
The problem of garbage is a significant issue in society that affects the environment and human well-being. The lack of knowledge and public awareness to dispose of garbage at its place, resulting in garbages accumulating and dispersing. This dedication is aimed at raising the concern of the people of the village of Bungkuk, Parang district of Magetan, about the importance ofining a clean and healthy environment. The method used is Asset Based Community Development (ABCD). The ABCD approach involves five steps, including the process of discovery, dream, planning, setting up, and implementation. The initial step given by the students of KPM 19 in creating a clean and healthy environment in the village of Bungkuk is by giving a garbage bathtub. The garbage cans are placed at certain points, and colored to distinguish between organic and non-organic waste. Based on our surveys, there's an increase in the population towards proper disposal of garbage. The surroundings are becoming cleaner and more natural, and the scattered garbage is starting to decrease slightly. Garbage bathing activities have a positive impact in the realization of environmental hygiene and public participation in the management of garbage. Public awareness is also rising.